Pendampingan Masyarakat Dalam Pembuatan & Mengembangkan Bisnis Creamy Mango Delight Pada Kelurahan Tondon Mamullu - Lisa K Wibisono; Marson Palloan; Rapi Kada Pane (OPTIMAL Jurnal Ekonomi dan Manajemen, 2021)
The trend of dessert development can be a source of inspiration for promising business opportunities because it has its own trends and markets in the community. Generally, people consume mangoes directly without processing them first, therefore, we innovate to turn these mangoes into desserts, namely Creamy Mango Delight. Creamy Mango Delight not only sells a creamy and delicious taste but also sells the beauty of its beautiful appearance. So this activity aims to develop mangoes into processed desserts and provide new knowledge in marketing products in the Tondon Mamullu village